(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Feminine sensibility is a woman’s feelings and emotions about her own problems. It also illuminates her psychology and hankerings. The core tenet of feminism is the notion that women are mistreated in all spheres of society, especially in the realms of politics and the economy, in terms of men. The history of the human species begins with the female, as she is the carrier of the first human chromosome. Regrettably, generations of historians have viewed "Man" as the main character when, in reality, it is the woman who deserves the title. Her work, expertise, and biology, which hold the key to determining the course of events for the whole human race, will determine the course of events for the future of mankind. Jai Nimbkar was born in Pune to a very affluent family of Maharashtrian origin. It is well-known for its social and cultural responsibilities. Her novel Temporary Answers demonstrates women’s significant role and responsibilities in society, emphasising that women should be granted equal status, defying the constraints of tradition, gender discrimination, and humiliation. This study sheds insight into the novel’s depiction of its female protagonist, including her struggle for independence, innate femininity, and defiance of patriarchy.